Spider-Man : amazing - Tobin, Paul, 1965-; Lolli, Matteo; Koblish, Scott (New York : Marvel, 2010)
While writing an article for her school paper, Gwen Stacy follows the adventures of Spider-Man as he takes on Midnight, Bullseye, and other villains. Then, Spider-Man joins the Blond Phantom Detective Agency as they follow Wolverine around town.
"Contains material originally published in magazine form as Spider-Man #1-4"--Cover p. [2].
Cover title: Marvel adventures Spider-Man
Young Adult
Keywords: Spider-Man (Fictitious character) -- Comic books, strips, etc. -- Juvenile fiction; Superheroes -- Comic books, strips, etc. -- Juvenile fiction; Good and evil -- Comic books, strips, etc. -- Juvenile fiction; New York (N.Y.) -- Comic books, strips, etc. -- Juvenile fiction; Spider-Man (Fictitious character) -- Fiction; Superheroes -- Fiction; Good and evil -- Fiction; New York (N.Y.) -- Fiction; Cartoons and comics; Spider Man (Fictional character) -- Comic books, strips, etc. -- Fiction; Superheroes -- Comic books, strips, etc. -- Fiction; Good and evil -- Comic books, strips, etc. -- Fiction; New York (N.Y.) -- Comic books, strips, etc. -- Fiction; Superhero graphic novels; Comic books, strips, etc; Graphic novels; Superhero comic books, strips, etc; Graphic novels